Effect of mulberry leaf or mulberry leaf extract on glycemic traits: a systematic review and meta-analysis. Issue 3 (16th January 2023) - Cui, Wenyu; Luo, Kaiyun; Xiao, Qian; Sun, Zhaoyue; Wang, Yunfu; Cui, Caifang; Chen, Fuchun; Xu, Ben; Shen, Weijun; Wan, Fachun; Cheng, Anwei
Abstract : Meta-analysis indicated that the supplementation of mulberry leaves or mulberry leaf extract is beneficial for regulation of the glycemic indices, including fasting blood glucose, glycosylated hemoglobin, and fasting plasma insulin. Abstract : Mulberry leaf (ML) and mulberry leaf extract (MLE) have numerous biological properties, such as regulating sugar and lipid metabolism, reducing blood glucose, and increasing insulin secretion. The aim of this study was to perform a systematic review and meta-analysis of randomized clinical trials to examine the effect of ML/MLE supplementation on glycemic traits in adults, including fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), and fasting plasma insulin (FPI). Twelve clinical trials (615 participants) fulfilled the eligibility criteria for the present meta-analysis, which included sensitivity analysis and GRADE (grading of recommendations assessment, development, and evaluation) certainty. Based on the heterogeneity between included studies, a random effects model was applied in the meta-analysis, and the results are expressed as WMD (weighted mean differences) with 95% CI (confidence intervals). Meta-analysis showed that ML/MLE supplementation resulted in a significant reduction in FBG by −0.47 mmol L −1, HbA1c by −2.92 mmol mol −1, and FPI by −0.58 μIU mL −1 . In addition, subgroup analysis indicated that long-term supplementation of ML/MLE (≥8 weeks) was more effective for regulation of the glycemic traits in the non-healthy and baseline FPG >6.1 mmol L −1 subgroups. Glycemic regulation by ML/MLE may be attributed to the phytochemicals they contain, which are mainly 1-deoxynojirimycin, flavonoids, phenolics, and polysaccharides.